Shinju : el teatro del amor en "Patriotismo" de Yukio Mishima y "Suicidio por amor" de Yasunari Kawabata (2017)
"In 17th century Japanese literature the theme of shinju, also known as "love suicide" or "double suicide" in English, became central thanks to the great popularity of bunraku theatre. In this literary theme, the lovers, whose love is forbidden, commit suicide in order to achieve the desired union in the afterlife. In shinju stories prohibition is at the same time what leads lovers to suicide and what makes their deaths tragic, allowing the lovers to be represented as martyrs and their love to be sublimated. Yukio Mishima's nouvelle "Patriotism" (1960) and Yasunari Kawabata's short story "Love suicides" (1926) talk about the double suicide of married couples whose union is not forbidden. In both cases, the stories can be considered love suicides (shinju) but linked to a love that differs from the one ascribed to the suicide lovers of 17th century theatre plays." -- Tomado del Formato de Documento de Grado.